2014
DOI: 10.1039/c4cp01860e
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption structures of non-aromatic hydrocarbons on silicalite-1 using the single-crystal X-ray diffraction method

Abstract: The actual adsorption structures of non-aromatic hydrocarbons on the MFI-type zeolites have not yet been determined. This is due to the presence of twinning, which makes crystallographic analysis difficult. We recently overcame this problem, and now report the various adsorption structures of n-butane, n-pentane, n-hexane, 1-butene, cis and trans-2-butene, 2-butyne and isopentane on silicalite-1 (MFI-type zeolite) as determined via single-crystal X-ray diffraction. The structures were elucidated for both low a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Recently, we have reported the adsorption structures of C 4 -C 6 hydrocarbons (Fujiyama, Seino et al, 2014). Linear 2butyne prefers the straight channel, and bent n-butane prefers the sinusoidal channel as expected.…”
Section: Resultssupporting
confidence: 66%
“…Recently, we have reported the adsorption structures of C 4 -C 6 hydrocarbons (Fujiyama, Seino et al, 2014). Linear 2butyne prefers the straight channel, and bent n-butane prefers the sinusoidal channel as expected.…”
Section: Resultssupporting
confidence: 66%
“…Conventional porous adsorbents, such as zeolites and activated carbons, have been used extensively in pressure and/or temperature cyclic configurations. Nevertheless, the disadvantages of low linear/branched isomer separation selectivity and the small uptake capacity of conventional adsorbents limit their practical applications 7,11,19,20 . Among the porous materials, metal–organic frameworks (MOFs) consisting of metal ions/clusters and organic ligands, have triggered enormous research interests due to their great potential to address the ongoing challenges pertaining to physisorption‐based applications 21‐24 .…”
Section: Introductionmentioning
confidence: 99%
“…In order to simplify the analysis, only zeolites that possess straight channels are considered in this work. Although previous studies have demonstrated that the shape traced by the channel path (e.g., straight, sinusoidal) influences alkane adsorption behavior, [19][20][21][42][43][44] zeolites with channels that do not trace straight paths have been omitted because of their small number in the database. However, even among zeolites having only straight channels, the atoms that comprise the channel openings may connect to form circles, ovals, or other shapes, and these shapes are expected to influence the adsorption thermodynamics.…”
Section: Effects Of Channel Diameter and Cross-section For Zeolites Wmentioning
confidence: 99%